Malay Online Virtual Integrated Corpus (MOVIC): a systematic review - Awang Abu Bakar, Normi Sham; Yaacob, Hamwira Sakti; Handayani, Dini; Abuzaraida, Mustafa Ali (IEEE Explore, 2018)
The development of the various Malay corpora have given the opportunities to many researchers to explore their usage in diverse contexts. However, the corpora were distributed in various locations, and for the ease of access for users, a system called Malay Online Virtual Integrated Corpus (MOVIC) is proposed. This paper focuses on applying the systematic literature review (SLR) on the Malay corpus research to find out the recent development in the area. From the initial search, 3231 articles were extracted from five online databases, such as, IEEE Xplore, Scopus, ProQuest, Springer Link, and ACM. After several rounds of filtering, 11 papers were selected for review.